(NiSTORIQ OPERYs (NiSTORIQs - (NkREM^MAR(B. (Ngs; (NgRA^EW(B. (Np(B.(Nw(B.s ((NmOSKWAs (N`RAJTs, 2025)
(NISTORIQ OPERY g(B. (NkRE^MARA(B-(NBIBLIOGRAFI^ESKIJ RARITET(B, (NNADELENNYJ HARAKTERNOSTX@(B,(NQRKOSTX@ I SUB_EKTIWNOSTX@ IZLOVENIQ(B.s
Keywords: (NISTORIQs